Addressing psychosomatic symptom distress with mindfulness-based cognitive therapy in somatic symptom disorder: mediating effects of self-compassion and alexithymia - Xu, Lianrong; Shi, Jihong; Li, Chengwen (Frontiers in Psychiatry, 2024)
Objective: This study explored the association between self-compassion, alexithymia, and psychosomatic symptom distress in a clinical sample of somatic symptom disorder (SSD) participating in a mindfulness-based cognitive therapy (MBCT) program. Methods: One hundred and sixteen SSD patients who participated in an MBCT program with completed interventions ≥ 4 sessions were included into a retrospective analysis (76.7% female, mean age = 40.0, SD = 9.5). Psychometric measures of psychosomatic symptom distress (Brief Symptom Inventory-18 Global Severity Index (BSI-GSI)), self-compassion (Self-Compassion Scale (SCS)), and alexithymia (Toronto Alexithymia Scale (TAS)) were collected upon admission to the MBCT program and at 6-month follow-up following treatment inclusion. Results: Serial mediation analysis (MBCT→ΔSCS→ΔTAS→ΔBSI-GSI) suggested that both changes in self-compassion and alexithymia had significant indirect effects on improvement in psychosomatic distress (ΔSCS β = -1.810, 95% bootstrap CI (-2.488, -1.160); ΔTAS β = -1.615, bootstrap 95% CI (-2.413, -0.896); ΔSCS→ΔTAS β = -0.621, bootstrap CI (-1.032, -0.315)). Furthermore, a post hoc analysis in a reverse sequence (MBCT→ΔTAS→ΔSCS→ΔBSI-GSI) revealed that reduction in alexithymia improved psychosomatic distress, and that increase in self-compassion was a subsequent outcome of alexithymia alleviation (ΔTAS β = -2.235, bootstrap 95% CI (-3.305, -1.270); ΔSCS β = 0.013, 95% bootstrap CI (-0.600, 0.682); ΔTAS →ΔSCS β = -1.823, bootstrap CI (-2.770, -1.047)). Conclusion: Both alexithymia alleviation and self-compassion improvement play a mediating role on reducing psychosomatic distress in SSD patients following an MBCT program. Self-compassion improvement might be a subsequent outcome of MBCT-related alexithymia alleviation.